Are online discussion forums useful platforms for paediatric surgeons to seek advice regarding patient management? A review of the queries posted on the world federation of association of pediatric surgeons facebook group (The Pediatric Surgeon's Lounge) - Sachit Anand; Shilpa Sharma; Sameh Shehata (Wolters Kluwer Medknow Publications, 2022)
Background: Social media platforms are popular places for discussing difficult cases amongst the surgeons. Paediatric Surgeon's Lounge (PSL) is a closed Facebook group for the interaction of paediatric surgeons from different parts of the world. We aim to assess the safety and utility of the responses given by the members of the PSL group to the queries about the management of paediatric surgical cases. Methods: All posts on PSL between January and July 2021 were retrospectively screened to select the patient management-related queries. For each included query, all the responses were scrutinised for their utility and safety. The utility was categorised as helpful or not helpful, and the safety of these responses was categorised as safe or unsafe. A note was also made whether any unsafe response was rectified in the subsequent responses or not. The proportion of each response category was calculated. Results: Twenty-two queries with a total of 353 responses were assessed. The median (range) number of responses per query was 10 (2-45). The proportion of helpful, safe and rectified unsafe responses was 91.5% (307/353), 96.8% (342/353) and 36% (4/11), respectively. Conclusions: PSL is a safe and helpful platform for taking advice regarding the management of paediatric surgical cases.